(untitled) (Research, Society and Development, 2019)
Recent research has shown a growing interest in iron oxide magnetic nanoparticles because they can be applied in many areas. These nanoparticles can be produced by different methods, such as, co-precipitation, microemulsion, hydrothermal, sol-gel, among others. In these synthetic processes, toxic solvents and surfactants are often used. Those could be avoided using green synthesis, in which the toxic products are replaced by green materials (fruit peels and plant leaves), this type of synthesis decreases the cost of production of the nanoparticles and it is considered environmentally friendly when the interest is the removal of contaminants in water. By eliminating remaining toxic products from the synthetic pathway nanoparticles are considered biocompatible and can be used in biomedicine. In this way, this work aims to carry out a bibliometric analysis on the use of green synthesis in the production of iron oxide magnetic nanoparticles. The bibliometric analysis was performed by collecting articles in the Web of Science database. From the reading of these articles it was possible to verify the countries that publish the most in the area: Iran, India and China respectively, due to the strong investments in the field of nanotechnology. The research also showed that this type of synthesis is a recent topic among the researchers, it was also possible to verify the green materials that are currently used in the green synthesis of iron oxide magnetic nanoparticles.